# If for non-zero x, $af(x)+bf(\dfrac{1}{x})=\dfrac{1}{x}-5$ where a not equal to b, then find f(x).

Verified

143.7k+ views

**Hint:**Replace x with $\dfrac{1}{x}$ in the given equation and then equate to find the answer.

**Complete step-by-step answer:**Given,

$af(x)+bf(\dfrac{1}{x})=\dfrac{1}{x}-5$………(1)

On replacing x by 1/x in the equation we get,

Therefore, after replacing we get,

$\Rightarrow af(\dfrac{1}{x})+bf(x)=x-5$………. (2)

Now for the next step we multiply eq (1) with a and eq (2) with b we get,

$\Rightarrow a^2f(x)+abf(\dfrac{1}{x})=\dfrac{a}{x}-5a$………… (3)

$\Rightarrow abf(\dfrac{1}{x})+b^2f(x)= \dfrac{b}{x}-5b$……. (4)

Now for the next part of the solution we.

Subtract (4) from (3), on doing that we get,

$\Rightarrow (a^2-b^2)f(x)= \dfrac{a}{x}-\dfrac{b}{x}-5a+5b$

Now on simplifying we get,

$\Rightarrow (a-b)(a+b)f(x)=(a-b) \dfrac{1}{x}-5(a-b)$

On taking f(x) as the subject of the formula we get,

$\Rightarrow f(x)=(\dfrac{1-5x}{x(a+b)})$

Before this is the answer to the question,

**Therefore, $f(x)=(\dfrac{1-5x}{x(a+b)})$ is the correct answer.**

**Note:**Students often make mistakes in the every step of the question. They are not able to substitute x with the correct variable in the equation. Put correct value while moving to the next step.